Tppp3 determines basal body positioning and identity of respiratory cilia via microtubule assembly and sphingolipid homeostasis - Takafumi Sakai; Masahiro Kawakita; Arashi Seki; Katsuyoshi Takaoka; Misaki Kurata; Junpei Torikai; Sohshiroh Atsumi; Kanji Yawata; Kentaro Noi; Yosuke Fukutani; Keiichi Noguchi; Hirofumi Kiyokawa; et al. (Proceedings of the National Academy of Sciences, 2025)
Cilia are hair-like organelles that protrude from the cell surface. In mammals, tracheal multiciliated cells (MCCs) play an important role in elimination of hazardous microorganisms by driving a unidirectional mucus flow. Although uniform orientation of ciliary beating is critical for the unidirectional flow, it remains unknown how MCCs establish uniform orientations and maintain identities of hundreds of ciliary membranes. This study focuses on investigating the roles of Tubulin Polymerization Promoting Family Member 3 (Tppp3) in MCC function. We generated a Tppp3-deficient mouse ( Tppp3 ∆ex2-4/∆ex2-4 ; Tppp3 knockout (KO)) and found that the Tppp3 KO mouse exhibited cough and hyposmia phenotype. The loss of Tppp3 disrupted the apical microtubules (MTs) meshwork in the tracheal MCCs, leading to random orientation and alignment of basal bodies (BBs) of the motile cilia. Unexpectedly, aberrant ciliary membrane fusions occurred in the trachea of the Tppp3 KO mice. We examined the underlying molecular mechanism of the ciliary membrane fusion by isolating the tracheal cilium. Liquid Chromatography-Mass Spectrometry (LC–MS) analysis as well as pharmacological analysis revealed that hyperaccumulation of a long chain ceramide at the ciliary membrane caused the membrane fusion. In addition, sensory cilia formation was impaired in the olfactory sensory neuron of the Tppp3 KO mice. Due to the lack of Tppp3, dendritic MT assembly that underlies long-range migration of BBs toward the cell surface was impaired. These findings demonstrate that Tppp3, as well as the defined intracellular MT architecture, regulate proper orientation/subcellular positioning of BBs and the independency of individual motile cilium membranes.